Isothermal modelling of the adsorption of lead II onto activated carbon from Tridax procumbens - Ubana, Muhammed Abdullahi; Ya'u, Murtala; Basirun, Ain Aqilah; Yasid, Nur Adeela; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
Hypertension and kidney damage have been linked to lead exposure in adults. Any person can be harmed by lead, but pregnant women and their unborn children are especially vulnerable. Presently, lead pollution is removed using membrane separation, ion exchange, precipitation, and biosorption. Biosorption's low operating costs, high efficiency at detoxifying low concentrations of toxicants, and small volume of disposal materials make it the least problematic of these technologies. The biosorption of lead (II) onto activated carbon from Tridax procumbens is remodeled using nonlinear regression and the optimal mode was determined by a series of error function assessments. The Freundlich model performed best in statistical tests including root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), and corrected Akaike Information Criterion (AICc) The calculated Freundlich parameters kF value using nonlinear regression was 1.334 (1/g) (95% confidence interval from 0.821 to 1.847) and nF value of 3.872 (95% C.I. from 1.972 to 5.771). Modelling using a nonlinear approach allows for the calculation of uncertainty range in terms of 95% confidence interval that would be useful for model comparison and discriminant in future studies.